Factorize : a² + b² + 2( ab + bc + ca)
Answers
Answered by
7
Solution : a² + b² + 2ab + 2bc + 2ca
= (a² + b² + 2ab) + 2bc + 2ca
= (a + b)² + 2c( b+a)
= (a + b) (a + b) + 2c ( a + b )
= (a + b) [ (a +b) + 2c ]
= (a + b) ( a + b + 2c )
________________
Answered by
1
Here you go!
sorry for the wrong answer last time...
my sister did that......
Attachments:
![](https://hi-static.z-dn.net/files/d0d/6840a4128f67bdcb2790757bdb439a3b.jpg)
Similar questions
Math,
5 months ago
Math,
5 months ago
English,
10 months ago
Social Sciences,
10 months ago
Physics,
1 year ago